Analisis Usability Testing Menggunakan Metode SUS (System Usability Scale) Terhadap Kepuasan Pengguna dalam Mengakses Website Tokopedia - Silviyani Salsabilla; Putri Isti Adzani; Wisnu Trilaksa Riyanto; Yayan Suryana; Rasya Juang Adytya Perkasa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Transactions with media to sell goods or services Computer networks connected to the internet are called and electronic commerce. The development of e-commerce in Indonesia Due to the large population of Indonesia, it is very high Very large. Tokopedia is an e-commerce company Currently the most popular market format in Indonesia. This study aims to analyze the usability and user satisfaction of the Tokopedia application using the System Usability Scale (SUS) method. The method involves the use of specific questions to participants and a Likert scale to measure their responses. The results show that application speed is a factor that can affect user satisfaction. The quality of information, features, and completeness of the seller and buyer pages scored high, indicating that users are satisfied with the features and services provided by the Tokopedia application. Increasing the speed of the application can increase user satisfaction, while the quality of information, features, and completeness of the seller and buyer pages are already satisfactory and the Tokopedia Website as a whole is acceptable.